Analisis Pengaruh Sistem Keamanan Informasi Perbankan Pada Nasabah Pengguna Internet Banking - Dianta, Indra Ava; Zusrony, Edwin (Universitas Nusantara PGRI Kediri, 2019)
A secure banking world service is an absolute requirement to compete competitively in today's digital age. Information system security in banking services transaction especially Internet Banking features become very important to support accountable service. In the information security system or computer there are 3 dimensions are assessed, namely confidentiality, integrity, and availability. The three dimensions applied to the respondents of employees of PT. XYZ Salatiga using Forum Group Discussion (FGD) technique. The results of this study show that most of the employees of PT. XYY Salatiga of 80%, stated that the availability dimension with the access speed indicator is the most affect the security of information system of Internet Banking feature. This can be a recommendation for Bank BCA in terms of increasing data security especially related to Internet Banking.